UTILIZATION OF CHICKEN EGG POWDER AS AN ADDITIONAL MATERIAL TO PRODUCE PAVING BLOCK - Masthura Masthura; Abdul Halim Daulay; Purnama Indah Lase (Universitas Islam Negeri Sumatera Utara Medan, 2021)
Abstract: Research has been carried out on the analysis of the physical properties of paving blocks from egg shell powder. This study aims to determine the physical properties of water absorption, density and porosity in the resulting paving blocks. The samples used were eggshell powder, cement, and sand with a ratio of 0%:40%:60%, 5%:35%:60%, 10%:30%:60%, 15%:25%:60%, 20%:20%:60%. The FAS used was 0,56 and the drying time for the paving blocks was 28 days. The results of the analysis of the physical properties of paving blocks produced at 0% variation have a water absorption value = 8,08%, density = 2,29 g/cm3 and porosity = 13,31%, at 5% variation has a water absorption value = 8,10%, density = 2,18 g/cm3 and porosity = 13,94%, the 10% variation has a water absorption value = 8,63%, density = 2,17 g/cm3 and porosity = 14,41% , the 15% variation has a water absorption value = 8,83%, density = 2,16 g/cm3 and porosity = 14,94%, the 20% variation has a water absorption value = 9,10%, density = 2 ,14 g/cm3 and porosity = 16,82%. Keywords: Paving Block, Eggshell Powder, Physical Properties.